Hodgkin Lymphoma Presenting as Cardiac Tamponade in a Young Female - Georgia Kaiafa; Stylianos Daios; Stavroula Bountola; Triantafyllia Koletsa; Michail Makris; Charikleia Chatzikosma; Antonia Loukousia; Vasileios Perifanis; Antonios Ziakas; Christos Savopoulos (Case Reports in Hematology)
Hodgkin lymphoma (HL) is an uncommon malignancy that is characterized by Hodgkin or Reed–Sternberg cells. Cardiac implications of HL remain one of the least investigated subjects. There are few case reports in the literature of cardiac tamponade in HL patients. We describe a case of a 21-year-old female patient who presented with cardiac tamponade as an initial presentation of HL. Any pericardial effusion significant for tamponade requires immediate drainage and fluid analysis for thorough investigation. Prompt identification and timely intervention are crucial in effectively addressing these complex situations. Therefore, clinicians should maintain heightened awareness in such cases.